Classroom activities manual [for] Effective human relations in organizations seventh edition - Reece, Barry L.; Brandt, Rhonda (Boston : Houghton Mifflin, 1999)
Introduction to human relations. Improving personal and organizational communications. Understanding your communication style. Building high self-Esteem. Personal values influence ethical choices. Attitudes can shape your life. Motivating yourself and others. Building trust with constructive self-disclosure...
Keywords: Psychology; Personnel management; Personnel management; Psychology, Industrial; Interpersonal relations